Identification of Specific Inhibitors of Trypanosoma cruzi Malic Enzyme Isoforms by Target-Based HTS - Ranzani, Americo T. (2017)
Trypanosoma cruzi is the causative agent of Chagas disease. The lack of an efficient and safe treatment supports the research into novel metabolic targets, with the malic enzyme (ME) representing one such potential candidate. T. cruzi expresses a cytosolic (TcMEc) and a mitochondrial (TcMEm) ME isoform, with these activities functioning to generate NADPH, a key source of reducing equivalents that drives a range of anabolic and protective processes. To identify specific inhibitors that target TcMEs, two independent high-throughput screening strategies using a diversity library containing 30,000 compounds were employed. IC50 values of 262 molecules were determined for both TcMEs, as well as for three human ME isoforms, with the inhibitors clustered into six groups according to their chemical similarity. The most potent hits belonged to a sulfonamide group that specifically target TcMEc. Moreover, several selected inhibitors of both TcMEs showed a trypanocidal effect against the replicative forms of T. cruzi. The chemical diversity observed among those compounds that inhibit TcMEs activity emphasizes the druggability of these enzymes, with a sulfonamide-based subset of compounds readily able to block TcMEc function at a low nanomolar range.